(untitled) (Applied Biological Research, 2024)
Essential oils are most frequently used as natural repellents against a variety of insect pests in contrast to the synthetic repellents. Honeybees are susceptible to most of the toxic insecticides in the environment. In the present study, the repellent activity of citronella (Cymbopogon nardus) and clove bud (Syzygium aromaticum) bud oils was assessed against worker bees of Apis dorsata through electroantennogram (EAG), olfactometer by exposing bees in laboratory conditions. EAG studies showed that, the bees responded to both the essential oils and the mean antennal responses of worker bees towards citronella and clove bud oils were 0.74 ± 0.23 and 0.67 ± 0.21 mV, respectively. Comparatively, citronella showed better antennal responses than clove bud oil. The dual choice behavioural responses of bees showed 100% repellency against citronella in contrast to 80% repellency and only 20% attraction towards the clove bud oil. The field studies showed that application of citronella on the surface of the combs gradually repelled the bees. The present study concludes that citronella is a potential essential oil in repelling the A. dorsata colonies.